Identification of the workplace basic skills necessary for effective job performance by entry-level workers in small businesses in Oklahoma. - Gerald W. Harris (Adult Education Research Conference, 1997)
A modified Delphi technique was used to identify the workplace basic skills needed by employees in small businesses employing 50 or fewer workers. Employers rated a list of 36 skills from the SCANS Report, in importance, on a scale from 1-little importance to 10-extreme importance. The ratings along with written comments and verbal responses to preplanned questions in phone interviews were used to determine if the SCANS skills could be validated for small businesses in Oklahoma.